A rare type of single coronary artery with right coronary artery originating from the left circumflex artery in a child - Jong Min Kim; Ok Jeong Lee; I-Seok Kang; June Huh; Jinyoung Song; Geena Kim (Korean Pediatric Society, 2015)
The presence of a single coronary artery is a rare congenital anomaly; such patients often present with severe myocardial ischemia. We experienced the case of a 13-year-old girl with the right coronary artery originating from the left circumflex artery. She visited our Emergency Department owing to severe chest pain; her cardiac enzyme levels were elevated, but her initial electrocardiogram (ECG) was normal. Echocardiography showed normal anatomy and normal regional wall motion. When she presented with recurrent chest pain on admission, the ECG showed significant ST-segment elevation in the left precordial leads and inferior leads with ST-segment depression in aVR lead, suggesting myocardial ischemia, and her cardiac enzyme levels were also elevated. We performed coronary angiography that showed a single right coronary artery originating from the left circumflex artery without stenosis. We confirmed the presence of a single coronary artery using coronary computed tomography. In addition, the treadmill test that was performed showed normal results. She was discharged from the hospital without any medications but with a recommendation of a regular follow-up.